Bridging the Archipelago: E-Governance and Access to Public Services in Sulu, Philippines - Datu Ansaruddin K. Kiram; Mharcelyn M. Kiram; Adzlan P. Hamsaji (Enigma Institute, 2024)
Geographic isolation, socioeconomic challenges, and security concerns have historically hindered public service delivery in Sulu, Philippines. This study investigated the role of e-governance in bridging this gap and enhancing citizen engagement with government services. A mixed-methods approach was employed. Quantitative analysis of government records assessed service utilization pre- and post-implementation of e-governance initiatives. A survey of 300 Sulu residents evaluated experiences with e-governance platforms. Qualitative data from semi-structured interviews with citizens and government officials provided contextual insights. E-governance platforms significantly increased public service utilization. Citizens reported improved convenience, reduced travel time and costs, and greater transparency. Challenges include digital literacy, limited internet connectivity, and trust in online platforms. In conclusion, e-governance has the potential to improve service access in Sulu. Successful implementation requires addressing infrastructure limitations, promoting digital literacy, and building trust in online services. This study informs strategies for leveraging technology for inclusive service delivery in marginalized communities.